Karakteristik Mortar Geopolimer Abu Sawit Dengan Variasi Modulus Aktivator - Halinda Putri, Winda Astuti; Olivia, Monita; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Geopolymer is an environmentally friendly alternative construction material that is made from activation of source material with rich in silicon (Si) and alumunium (Al) by alkaline activator solution. This research using palm oil ash from Riau Province as based geopolymer mortar. Properties of geopolymer mortar that was studied based variation of modulus activator, dosage activator, curing temperature, type of processing ash, and rest period. Research showed that increasing compressive strength of geopolymer mortar influenced by increasing modulus activator, dosage activator, and curing temperature with optimum condition, as well as combustion of palm oil ash in furnace, and rest period of geopolymer mortar for 3 days. Â Keywords: palm oil ash, geopolymer, modulus activator, dosage activator